How realism promotes better social outcomes than empiricism and subjective idealism - Stegmann, Juan Pablo (Studia Philosophiae Christianae, 2019)
This paper proposes a conceptual model that fosters interdisciplinary thinking and critical thinking by connecting the three main philosophical traditions that impact modern thinking – British empiricism, Continental Europe subjective idealism, and realism – with their epistemological foundations and in combination with modern social disciplines: ethics, social responsibility, and political economy. Through a statistical analysis this paper shows which of the three epistemologies produces better social outcomes.